2017
DOI: 10.18632/oncotarget.21978
|View full text |Cite
|
Sign up to set email alerts
|

“Paradoxical” findings of tumor vascularity and oxygenation in recurrent glioblastomas refractory to bevacizumab

Abstract: Anti-angiogenic therapy induces the apparent normalization of vascular structure, decreases microvessel density (MVD), and improves tumor oxygenation in glioblastomas (GBMs). Six initial and recurrent tumor pairs after bevacizumab (Bev) treatment were compared with GBMs from nine patients resected under neoadjuvant Bev treatment with regard to histological characteristics; MVD; MIB-1 index; and expression of vascular endothelial growth factor (VEGF) and its receptors, hypoxia markers (hypoxia-inducible factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 32 publications
5
35
2
1
Order By: Relevance
“…Hypoxia‐inducible factor‐1α was also able to activate the expression of PD‐L1 by binding of HIF to a specific hypoxic response element in the promoter of PD‐L1 in cancer cells . We have previously reported that Bev improves tumor oxygenation in glioblastomas, and that tumor hypoxia is regained in the post‐Bev refractory tumors, to a similar or even higher level compared with the paired pre‐Bev initial tumors . In the present study, however, immunosuppressive cells and molecules in the tumors of refractory Bev group were still suppressed compared with the naïve Bev group despite recovery of hypoxia.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…Hypoxia‐inducible factor‐1α was also able to activate the expression of PD‐L1 by binding of HIF to a specific hypoxic response element in the promoter of PD‐L1 in cancer cells . We have previously reported that Bev improves tumor oxygenation in glioblastomas, and that tumor hypoxia is regained in the post‐Bev refractory tumors, to a similar or even higher level compared with the paired pre‐Bev initial tumors . In the present study, however, immunosuppressive cells and molecules in the tumors of refractory Bev group were still suppressed compared with the naïve Bev group despite recovery of hypoxia.…”
Section: Discussioncontrasting
confidence: 59%
“…42,43 We have previously reported that Bev improves tumor oxygenation in glioblastomas, 4 and that tumor hypoxia is regained in the post-Bev refractory tumors, to a similar or even higher level compared with the paired pre-Bev initial tumors. 5 In the present study, however, immunosuppressive cells and molecules in the tumors of refractory Bev group were still suppressed compared with the naïve Bev group despite recovery of hypoxia. The expression of immune checkpoint molecules and immunosuppressive cells were strongly associated with VEGF-A.…”
Section: Effect Of Continuous Vegf Blockade Vs Recovery Of Hypoxia contrasting
confidence: 61%
See 3 more Smart Citations